Climate and cartography of the Pyrenees: the temperature map.: Map - Barrao Simorte, Samuel; Cuadrat Prats, José María; Serrano Notivoli, Roberto (Geographicalia, 2023)
This work presents a detailed mapping of monthly mean temperatures in the Pirineos, based on a large single database, with quality control and homogenized for the whole mountain range, generated by the CLIMPY-OPCC project for the characterization of climate evolution, in which the three Pyrenean countries, France, Spain and Andorra, have collaborated. The information is provided in grid mode at a daily scale of 1 x 1 km resolution, which allows a good approximation to the analysis of spatial patterns and monthly temperature variations. The map shows a set of twelve rasters reflecting the average temperature of each month of the year for the period 1981-2015. The result of the work, in addition to contributing to the knowledge of the Pyrenean climate, aims to provide tools for scientific research, natural resource management and public awareness of climate change.